SOSIALISASI UU NO. 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN SEBAGAI UPAYA MENINGKATKAN KESADARAN BERLALU LINTAS BAGI PELAJAR - Muhammad Iftar Aryaputra; Endah Pujiastuti (Adi Widya : Jurnal Pengabdian Masyarakat, 2023)
The World Health Organization (WHO) as an agency of the United Nations, noted that in Indonesia, traffic accidents are the third leading cause of death after coronary heart disease and tuberculosis (TB). It is recorded that around 1.2 million people die each year in traffic accidents. Traffic accidents are the leading cause of death for adolescents, aged 15 to 29 years. Of this number, 73% are dominated by teenage boys. The number of traffic accidents among adolescents can occur due to several factors, one of which is the lack of understanding of adolescents about the laws and regulations governing traffic problems. In Indonesia, there is a law that regulates traffic, namely Law no. 22 of 2009. An understanding of the substance of the Traffic Law is deemed necessary for teenagers, especially for those who are still in high school. Therefore, this activity is one of the means to minimize the death rate among teenagers caused by traffic accidents, by increasing the knowledge and understanding of teenagers about Traffic laws. It is hoped that a better understanding of the Traffic Law, can reduce the number of traffic accidents among teenagers. Broadly speaking, the implementation method in this activity can be divided into three stages, first, namely pre-activity which includes licensing activities, surveys, and program preparation. Second, implementation starts with giving questionnaires before and after lectures and lectures. Third, evaluation, which includes the preparation of reports. The results of this activity showed an increase in the understanding of service participants regarding the Traffic Law and the forms of violations regulated in it. Keywords: Traffic Violations, Sanctions, Traffic and Highway Laws, Youth